"Dementia worry" in memory clinic patients not diagnosed with organic mental disorder. (18th March 2014) - Kessler, E.-M.; Südhof, J. K.; Frölich, L.
<x content-type="archive" xml:space="preserve">Abstract</x> In order to best meet the needs of their clientele, practitioners in memory clinics need information about the characteristics of patients who do not meet the criteria for diagnosis of an organic mental disorder such as vascular dementia, Alzheimer's disease (AD), or mild cognitive impairment (MCI). In particular, concern about having or developing dementia may prompt ``cognitively healthy'' people to visit memory clinics. In a pilot study, we investigated ``dementia worry'' (DW) in addition to the socio-demographic characteristics, physical health risk-factors and psychological symptoms of memory clinic patients for whom dementia and MCI diagnoses were excluded after a comprehensive diagnostic work-up. Dementia worry has recently been defined as an "emotional reaction to the perceived threat of developing dementia" (Kessler et al., 2012). Accordingly, DW consists of both emotions (e.g. fear) and cognitions (e.g. thoughts, ruminations) regarding the perceived threat of developing dementia. Our study was evaluated by the Ethical Committee of the Medical Faculty Mannheim, University of Heidelberg.